Kedah towards a developed state - Golam Hassan, Asan Ali (Penerbit Universiti Utara Malaysia, 2005)
“Kedah: Towards a Developed State” is a collection of articles that highlights strategies, recommendation and comments that should be considered and undertaken by the Kedah state government to achieve the target as a developed state by the year 2010. The papers cover many aspects such as development, finance, industry and foreign direct investment, tourism and education and many more. The Kedah Maju Action Plan which is a continuation of the Kedah Development Action Plan (1990 – 2000) covers the period from 2001 to 2010. It outlines the aggressive strategies that have and will be undertaken to accelerate the economic development of Kedah in order to attain the developed status by the year 2010. One of the most important goals of the plan is to achieve a sustained Gross Domestic Product (GDP) growth of 15% annually for ten straight years.